PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE “5E” BERBANTUAN LKS TERSTRUKTUR UNTUK MENINGKATKAN KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIKA - Putu Suarniti Noviantari (Jurnal Santiaji Pendidikan (JSP), 2015)
This study aimed at (1) improving the math reasoning and communicating skill of VIIIA students at SMP Negeri 3 Karangasem and (2) investigating the students’ responses towards the implementation of 5E Learning Cycle model assisted by structured student worksheet. This study was a classroom action research whisch was conducted in 3 cycles. Each cycle consisted of planning phase, action phase, observation/evaluation phase, and reflection phase. The subject of the study was 30 VIIIA students at SMP Negeri 3 Karangasem in the academic year 2013/2014. Math reasoning and communicating skill data were gathered through an essay test and the students’ response data was collected through a questionnaire. Afterwards, the data was analyzed by means of descriptive analysis. The findings revealed that the implementation of 5E Learning Cycle model assisted by structured student worksheet was able to improve the math reasoning and communicating skill of VIIIA students at SMP Negeri 3 Karangasem. It was proven by the mean score 23.06 (quite good) in cycle I turned into 28.57 (good) in cycle II, and it turned into 34.2 (very good) in cycle III. The students gave positive responses towards the implementation of 5E Learning Cycle model assisted by structured student worksheet which was proven by the mean score 35.7.